Earnings overseas and cash holdings - Nascimento, Madalena Correia Martins (2015)
I investigate the impact of foreign pre-tax income on the total amount of cash held by companies and on the amount of cash that is held in companies’ foreign subsidiaries. I also investigate the impact of the existence and amount of cash held on companies’ foreign subsidiaries in the composition of cash holdings in terms of risk and liquidity. Using a sample of 100 largest U.S. non-financial and non-utilities companies I find that companies with higher earnings overseas present higher cash reserves and invest a higher fraction of their cash in risky assets. My evidence suggests that companies have a different optimization strategy for cash overseas, in which precautionary motives are not the main driver for holding cash.